2011
DOI: 10.7763/ijtef.2011.v2.150
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Energy Consumption: Empirical Evidence from Pakistan

Abstract: Even though a number of studies have attempted to determine the relationship between energy consumption and economic growth role of financial development has not been considered for efficient energy consumption. At present Pakistan is coping with a serious energy problem. This paper attempts to determine the nature of relationship between energy consumption, financial development and economic growth in Pakistan for the period 1980-2009 by employing co-integration and error correction techniques, finally Grange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 5 publications
3
26
1
1
Order By: Relevance
“…When financial development stems from banking sector or stock market, greater financial development leads to an increase in energy consumption. This finding is consistent with the bulk of the financial development-energy literature (see, for example, Islam et al, 2013;Kakar et al, 2011;Ozturk and Acaravcı, 2012;Sadorsky, 2010Sadorsky, , 2011Xu, 2012).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 87%
“…When financial development stems from banking sector or stock market, greater financial development leads to an increase in energy consumption. This finding is consistent with the bulk of the financial development-energy literature (see, for example, Islam et al, 2013;Kakar et al, 2011;Ozturk and Acaravcı, 2012;Sadorsky, 2010Sadorsky, , 2011Xu, 2012).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 87%
“…For Pakistan, Kakar et al (2011) showed that financial development affects energy consumption in the long term but not in the short term. For nine Central and Eastern European frontier economies, Sadorsky (2011) showed a positive and significant relationship between financial development and energy consumption when financial development is measured by banking variables, such as bank deposits to GDP, financial system deposits to GDP, and liquid liabilities to GDP.…”
Section: Financial Development and Energy Consumption In Other Countriesmentioning
confidence: 99%
“…The existence of a long-run relationship was conditioned by the measure of financial development. Kaker, Khilji, and Khan (2011) applied a production function to examine the relationship between economic growth, financial development and energy consumption using Pakistani data. They concluded that the neutrality hypothesis between financial development and economic growth exists but energy consumption Granger causes financial development.…”
Section: Financial Development and Electricity Consumptionmentioning
confidence: 99%